2000
DOI: 10.1089/104454900314465
|View full text |Cite
|
Sign up to set email alerts
|

Recycling and Resensitization of Delta Opioid Receptors

Abstract: Exposure to opioids results in the activation of opioid receptors; this is follow ed by receptor endocytosis. Previously, we showed that delta opioid receptors undergo rapid agonist-mediated internalization and that mutations in the C-tail result in a substantial loss of agonist-mediated internalization. In this study, we investigated the fate of receptors following rapid internalization. We found that the majority of the wild type receptors recycled back to the surface after acute agonist treatment. The kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Although many studies have explored the fate of the endocytosed receptor using various candidate receptors, relatively few studies have focused on the fate of the agonist co-endocytosed with the receptor. Studies using peptide agonists, at least in the case of opioid receptors, have shown that the co-endocytosed agonist is recycled back to the surface or processed in an acidic compartment, depending on the length of agonist treatment (17,53). Relatively few studies have focused on the enzymes that are responsible for post-endocytic peptide agonist degradation, although a number of peptidases have been shown to be capable of hydrolyzing neuroendocrine peptides including opioid peptides (2,45,54,55).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many studies have explored the fate of the endocytosed receptor using various candidate receptors, relatively few studies have focused on the fate of the agonist co-endocytosed with the receptor. Studies using peptide agonists, at least in the case of opioid receptors, have shown that the co-endocytosed agonist is recycled back to the surface or processed in an acidic compartment, depending on the length of agonist treatment (17,53). Relatively few studies have focused on the enzymes that are responsible for post-endocytic peptide agonist degradation, although a number of peptidases have been shown to be capable of hydrolyzing neuroendocrine peptides including opioid peptides (2,45,54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Receptor Recycling-Recycling experiments were carried out as described previously (17). Briefly, F6, F6-ECE2, N2A-␦OR, and N2A-␦OR-ECE2 cells or primary cortical neurons (2 ϫ 10 5 cells) were seeded into each well of a 24-well polylysine-coated plate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to quantitate the level of receptors in brain regions by ELISA, a 3-fold serial dilution of CHO cells expressing receptors by adding CHO cells not expressing the receptor was carried out (the final cell number was kept constant at 3 ϫ 10 5 cells/well). Receptor number at each dilution was quantitated by ligand binding as described (27). A parallel set of wells were subjected to ELISA using the SA25 antibody.…”
Section: Discussionmentioning
confidence: 99%
“…4). The levels of cell surface receptors were examined by using anti-Flag or anti-myc antibodies by ELISA (21).…”
mentioning
confidence: 99%